The Role of Data Quality and User Experience in Increasing User Satisfaction in the Jember Regency One Data Portal Application - Fatimah, Siti; Qomariah, Nurul; Nyoman Putu Martini, Ni (International Journal of Management Science and Information Technology, 2024)
This research aims to explain the influence of data quality and experience on user satisfaction with the Data Application used in Jember Regency. The total population in the study was 11,667 who were State Civil Apparatus employees in the Jember Regency Government. The number of samples was determined as 117 people. The sampling method in this research uses purposive judgmental sampling, namely by determining certain criteria which aims to produce a sample that can logically be considered representative of the population based on the researcher's assessment. This research uses descriptive analysis, testing measuring instruments in the form of testing the validity and reliability of data, and testing research hypotheses. The research results show that the quality of data provided by the Jember Regency Satu Data Portal can have a very significant positive impact on user satisfaction. The user experience variable turns out to have a positive and significant influence on user satisfaction of the Jember Regency Satu Data Portal.